Evaluation of Students’ Chacarter Building Program on Entrepreneurship Theme in Elementary Schools Using the Discrepancy Model - Emaculata, Natalia Inggit; Dwikurnaningsing, Yari; Mawardi, Mawardi (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to evaluate the implementation of the Strengthening the Pancasila Student Profile Program (P5) with an entrepreneurship theme in elementary schools in Central Java Province, using the Discrepancy evaluation model. This evaluation study employed a mixed-methods approach, beginning with quantitative data presented in tables, followed by qualitative analysis. The research subjects included the school principals and classroom teachers for grades 4, 5, and 6 at SDN Tlompakan 01 in Semarang Regency and SDN Jejeruk in Blora Regency. Data collection techniques included questionnaires, observations, interviews, and document studies. Quantitative data were analyzed using descriptive statistics and presented in tables, while qualitative data were analyzed descriptively.Â The findings of the study revealed several gaps in various aspects of the P5 program at both schools. In the design aspect, the average gap at SDN Tlompakan 01 is 19.5%, and at SDN Jejeruk, it is 14.5%, both of which are categorized as low; however, infrastructure still requires improvement. In the installation aspect, the average gap at SDN Tlompakan 01 is 25%, while at SDN Jejeruk, it was 15.3%, indicating that the program installation at SDN Jejeruk is better, supported by a facilitator team. In the process aspect, the average gap at SDN Tlompakan 01 is 23.15%, while at SDN Jejeruk, it was 14%, indicating that the program implementation at SDN Jejeruk is more consistent and organized. In the product aspect, the average gap at SDN Tlompakan 01 was 16.7%, and at SDN Jejeruk, it was 11.16%, showing that the program implementation at both schools has met the expected goals, though reports need to be more in-depth and systematic. In the cost-benefit analysis aspect, the average gap at SDN Tlompakan 01 was 16.7%, while at SDN Jejeruk, it is 8.4%, indicating that the benefits for students are in line with the costs incurred, with SDN Jejeruk showing better cost-effectiveness. Overall, the P5 program at both schools has had a positive impact on the development of students' skills and entrepreneurial character. However, improvements in certain elements, such as reporting and supporting facilities, are still necessary to make the program more effective and to achieve better outcomes in the future.